A Template Model Explains Jerboa Gait Transitions Across a Broad Range of Speeds - Ding , Jiayu; Moore , Talia Y.; Gan, Zhenyu (Frontiers in Bioengineering and Biotechnology, 2022)
For cursorial animals that maintain high speeds for extended durations of locomotion, transitions between footfall patterns (gaits) predictably occur at distinct speed ranges. How do transitions among gaits occur for non-cursorial animals? Jerboas (Jaculus jaculus) are bipedal hopping rodents that frequently transition between gaits throughout their entire speed range. It has been hypothesized that these non-cursorial bipedal gait transitions are likely to enhance their maneuverability and predator evasion ability. However, it is difficult to use the underlying dynamics of these locomotion patterns to predict gait transitions due to the large number of degrees of freedom expressed by the animals. To this end, we used empirical jerboa kinematics and dynamics to develop a unified Spring Loaded Inverted Pendulum model with defined passive swing leg motions. To find periodic solutions of this model, we formulated the gait search as a boundary value problem and described an asymmetrical running gait exhibited by the jerboas that emerged from the numerical search. To understand how jerboas change from one gait to another, we employed an optimization approach and used the proposed model to reproduce observed patterns of jerboa gait transitions. We then ran a detailed numerical study of the structure of gait patterns using a continuation approach in which transitions are represented by bifurcations. We found two primary mechanisms to increase the range of speeds at which gait transitions can occur. Coupled changes in the neutral leg swing angle alter leg dynamics. This mechanism generates changes in gait features (e.g., touchdown leg angle and timings of gait events) that have previously been shown to induce gait transitions. This mechanism slightly alters the speeds at which existing gait transitions occur. The model can also uncouple the left and right neutral leg swing angle, which generates asymmetries between left and right leg dynamics. New gait transitions emerge from uncoupled models across a broad range of speeds. In both the experimental observations and in the model, the majority of the gait transitions involve the skipping and asymmetrical running gaits generated by the uncoupled neutral leg swing angle mechanism.